RehabilitationApplication of Fullerton test in assessment of the influence of movement rehabilitation on the overall physical fitness of patients with lung cancer - Barinow-Wojewódzki, Aleksander; Laurentowska, Maria; Domaszewska, Katarzyna; Michalak, Edyta; Paszkiewicz, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: In recent years, lung cancer has been the cause of around 1.1 million deaths worldwide. The pathological changes occurring in the lungs lead to disorders of airflow in pulmonary alveoli with different levels of intensity. The disorders of ventilation and gas exchange cause respiratory acidosis and are directly responsible for the decrease of the physical capability of the body. The aim of the paper was to evaluate the influence of different rehabilitation programs on the general physical fitness of patients under chemotherapy. Material and methods : The study involved 70 men of mean age 63. Before and after the rehabilitation, the physical fitness was evaluated using the Fullerton test. Three study groups were isolated, each of them involving a different level of intensity of rehabilitation. Results : In the first group there was in increase of muscle strength and of the flexibility of the upper limbs. The strength of the lower limbs did not change and in the test after the therapy the length of the covered distance got shorter. With the second group, the strength and flexibility of both upper and lower limbs increased, as did the covered distance. No significant changes in the values of the parameters noted before and after the therapy were noted. Conclusions : The program involving therapeutic exercises gave better results in the monitored parameters compared to rehabilitation treatment extended by endurance training.